Dance Therapy as an Alternative treatment for People with Eating Addiction in the Era of COVID-19 - Vincentius Stef Karel; Bintang R. Simbolon (Indonesian Institute for Counseling, Education and Theraphy, 2022)
Dance therapy is also able to increase the hormone endorphins. Psychologically, dance is a form of therapy in expressing emotions through appropriate movements so that it can make humans more discover the meaning of their choices so that eventually humans find happiness and humans can find friends who serve to enlighten itself. If someone is happy, then that person will feel happy and diligent to activate his body more to move. This activity can burn fat. Therefore, researchers can see that dance therapy is a form of therapy that reduces the dangers of eating addiction.